What drove tuna catches between 1525 and 1756 in southern Europe? - Ganzedo, U.; Zorita, E.; Solari. A. P.; Chust, G.; Del Pino, A. Santana; Polanco, J.; Castro, J. J. (ICES Journal of Marine Science, 2009)
From 1525 to 1756, catches of tuna in almadrabas (trapnets) fluctuated greatly, but the overall trend was a downwards one. The aim of this study is to assess the potential influence of climatic factors on tuna fishing. We performed time-series analysis of the climate over the years 1525–1756 and determined whether such events can be related to historical data on bluefin tuna catches in the almadrabas of Medina Sidonia. We used a generalized linear model to relate the tuna catches to climatic parameters. We carried out variance partitioning analysis of tuna catches to assess the relative contribution of climate from temporal autocorrelation. The temporal autocorrelation in tuna catches was used as a surrogate for the contribution of the population dynamics to variation in the catch series. The results indicated that climate accounted for up to 12.3% of the total variance, the temporal effects (autocorrelation) accounted for up to 38.8% of the total variance, and up to 35.7% of the catch was accounted for by the joint effect of the two components. The significant variance accounted for by climate suggests that low temperatures during the Maunder minimum (the so-called “The Little Ice Age”, years 1640–1715) may have reduced both recruitment and abundance of tuna in the North Atlantic and the Mediterranean. Our findings suggest that both environmental and population dynamic components played an important role in regulating the almadraba catches in Medina Sidonia.